# Calculating the Laplace transform of an arbitrary Bessel Function of the first kind

\documentclass[12pt]{article} \usepackage{eufrak} \usepackage{design_ASC} \usepackage{enumitem} \usepackage{hyperref} \usepackage{physics} \usepackage{siunitx} \usepackage{enumerate} \usepackage{amssymb} \usepackage{mathtools} \usepackage{yfonts} \usepackage{amsmath}

\title{Calculating the Laplace transform of an arbitrary Bessel function of the first kind} \date{}

\begin{document}

\maketitle

\noindent The Bessel function is defined by the solution of the following equation, named Bessel's differential equation,

$t^2 \frac{d^2 x}{d t^2} + t \frac{d x}{d t}+(t^2-\alpha^2)x=0, \quad \alpha \in \mathbb{C}$

which yields the following result

$J_{\alpha}(t)=\sum_{n=0}^{\infty} \frac{(-1)^n}{n!\Gamma (n+\alpha+1)} \left( \frac{t}{\alpha}\right)^{2n+\alpha}$

Taking the Laplace transform of this function is extremely laborious, so we'll take a different approach, namely, by taking the Laplace transform of the Bessel equation. Therefore we have

$\mathcal{L}\left[t^2 \frac{d^2 x}{d t^2} + t \frac{d x}{d t}+(t^2-\alpha^2)x\right](s)=0 \Leftrightarrow \frac{d^2}{ds^2}\mathcal{L}[x'']-\frac{d}{ds}\mathcal{L}[x']+\frac{d^2}{ds^2}\mathcal{L}[x]-\alpha^2\mathcal{L}[x]=0$

We set the initial conditions as $x(0)=1,\ x'(0)=0$, and we get

$\frac{d^2}{ds^2}(s^2\mathcal{L}[x]-s)-\frac{d}{ds}(s\mathcal{L}[x]-1)+\frac{d^2}{ds^2}\mathcal{L}[x]-\alpha^2\mathcal{L}[x]&=0 \Leftrightarrow \Leftrightarrow 2\mathcal{L}[x]+4s\mathcal{L}'[x]+s^2\mathcal{L}''[x] -\mathcal{L}[x]-s\mathcal{L}'[x]+\mathcal{L}''[x]-\alpha^2\mathcal{L}[x]&=0 \Leftrightarrow \Leftrightarrow (s^2+1)\mathcal{L}''[x]+3s\mathcal{L}'[x]+(1-\alpha^2)\mathcal{L}[x]=0$

Making the following change of variable $u=\sqrt{s^2+1}\mathcal{L}[x]$, simplifies the equation to

$u''\sqrt{s^2+1}+\frac{s}{\sqrt{s^2+1}}u'&=\frac{\alpha^2u}{\sqrt{s^2+1}}\Leftrightarrow (u'\sqrt{s^2+1})'=\frac{\alpha^2u}{\sqrt{s^2+1}} \Leftrightarrow\\[3pt] \Leftrightarrow u'\sqrt{s^2+1}(u'\sqrt{s^2+1})'&=\alpha^2u'u \Leftrightarrow \frac{1}{2}((u'\sqrt{s^2+1})^2)'=\frac{1}{2}\alpha^2(u^2)' \Leftrightarrow \\ \Leftrightarrow \sqrt{s^2+1}u'&=-\alphau \Leftrightarrow \int \frac{1}{u}du= \int -\frac{\alpha}{\sqrt{s^2+1}}ds\Leftrightarrow \ln(u)=\alpha\ln(\sqrt{s^2+1}-s) \Leftrightarrow \\ \Leftrightarrow u&=(\sqrt{s^2+1}-s)^{\alpha}$ Reverting the substitution and remembering that $x(t)$ is the solution to Bessel equation, we conclude that $\label{eq:3} \mathcal{L}[J_{\alpha}(t)](s)=\frac{(\sqrt{s^2+1}-s)^{\alpha}}{\sqrt{s^2+1}}$

\end{document}